Substitution of xylol by extra virgin coconut oil in the diaphanization stage of histological routine (Research, Society and Development, 2022)
Xylol is a compound used in histological processing, in the diaphanization step, and is a harmful solvent to public health and the environment. The aim of the study was to present an alternative methodology to the use of xylol, in the clearing stage of the histological routine I use extra virgin coconut oil. Rattus norvegicus ear, cerebellum and tongue fragments divided into five groups were used. The control group, cleared with xylol, the treated group I, with xylol and 30% coconut oil, the treated II with xylol and 50% coconut oil, the treated III with xylol and 70% coconut oil and the treated IV just with coconut oil. Slides from all groups and tissues were stained with Harris Hematoxylin and Eosin, as cerebellum slides were also stained with Phosphotungstic Hematoxylin and Eosin, as for tongue by Gomori's Trichrome and as ear by Orcein with Harris' Hematoxylin. Tissues derived not differentiated between groups in the process of diaphanization, blocking and staining, the clearing action of the oil maintained the tissue morphology and did not interfere with staining. We can demand that coconut oil is a promising substitute for the use of xylol in the diaphanization step, being a safer and low-cost alternative, without compromising tissue morphology and without interfering with the different colors used, in addition to minimizing the risks to public and environmental health.